Proceedings of the 31st Annual Computer Security Applications Conference 2015
DOI: 10.1145/2818000.2818032
|View full text |Cite
|
Sign up to set email alerts
|

On the Robustness of Mobile Device Fingerprinting

Abstract: Client fingerprinting techniques enhance classical cookie-based user tracking to increase the robustness of tracking techniques.\ud A unique identifier is created based on characteristic attributes of the client device and then used for deployment of personalized advertisements or similar use cases.\ud While fingerprinting performs well for highly customized devices (especially desktop computers), these methods often lack in precision for highly standardized devices like mobile phones.\ud \ud In this paper, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(3 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Additionally, researchers have performed large crawls of the web that confirm a steady growth of browser fingerprinting [1], [2], [9], [22]. While most of these studies focused on desktops, others demonstrated they could successfully fingerprint mobile device browsers [11], [14]. Finally, a study we conducted in 2016 confirmed Eckersley's findings, but observed a notable shift in some attributes [14].…”
Section: Background and Motivationsmentioning
confidence: 58%
“…Additionally, researchers have performed large crawls of the web that confirm a steady growth of browser fingerprinting [1], [2], [9], [22]. While most of these studies focused on desktops, others demonstrated they could successfully fingerprint mobile device browsers [11], [14]. Finally, a study we conducted in 2016 confirmed Eckersley's findings, but observed a notable shift in some attributes [14].…”
Section: Background and Motivationsmentioning
confidence: 58%
“…The authors Hupperich et al (2015) also identify five strategies that can be used to detect possible fraud or cyber-attacks over the fingerprint procedure:…”
Section: Related Workmentioning
confidence: 99%
“…Device fingerprinting is very popular in internet-connected general purpose computing devices to track user behaviour and application usage. Some of the interesting applications include browser fingerprinting for web analytics, user tracking, fraud detection and accountability [9,23,27] and have gained a significant interests from cyber-security community. While it is clear that device fingerprinting can bring a lot of benefits -especially for providing automated and customisable user experience -there are also concerns that it can pose security and privacy risks [29,39].…”
Section: Introductionmentioning
confidence: 99%